Prevalence of hyposalivation and associated factors in survivors of head and neck cancer treated with radiotherapy (Journal of Applied Oral Science, 2021)
Hyposalivation and sensation of dry mouth (xerostomia) are one of the most common adverse effects in the treatment of patients with head and neck cancer. Objective: This study evaluates the prevalence of late hyposalivation and associated factors in survivors of squamous cell carcinoma of the oral cavity, oropharynx, hypopharynx, or larynx treated with radiotherapy with or without concomitant chemotherapy. Methodology: A cross-sectional study was conducted with 88 patients who had concluded radiotherapy at least three months before the study, at a referral center for the treatment of head and neck cancer in the Southern region of Brazil. Hyposalivation was evaluated based on the stimulated salivary flow rate using the spitting method. Multivariate analysis using binary logistic regression was performed to determine the associations between hyposalivation and clinical and demographic variables. Results: Hyposalivation was found in 78.41% of the sample and the mean radiation dose was 63.01 Gy (±9.58). In the crude model of the multivariate analysis, hyposalivation was associated with higher doses of radiation (p=0.038), treatment with concomitant radiotherapy and chemotherapy (p=0.005), and time elapsed since the end of radiotherapy (p=0.025). In the adjusted model of the multivariate analysis, hyposalivation was only associated with dose and time elapsed. Patient who received higher doses of radiation had a 4.25-fold greater chance of presenting hyposalivation, whereas a longer time elapsed since the end of radiotherapy exerted a 75% protective effect against the occurrence of hyposalivation. Conclusion: Hyposalivation is a highly prevalence late-onset side effect of radiotherapy in patients treated for head and neck cancer, with a greater chance of occurrence among those who received higher doses of radiation and those who ended therapy less than 22 months before our study. Concomitant chemotherapy and radiotherapy does not seem to increase the chances of hyposalivation compared to radiotherapy alone.